A supervisão como dispositivo de desenvolvimento profissional e transformação de práticas - Mesquita, Elza (2017)
It is maintained that the exercise of the profession of teacher requires a multidimensional of knowledge, authorizing the emergence of a multiplicity of practices that allow to legitimize and sustain the professional performance of its actors, (trans) (in) forming them. It makes sense, in the initial formation of teachers, to speak of pedagogical supervision as the need to obtain answers by the need to raise questions. Our concern for this study is based on the following starting point: to what extent do the supervisory models adopted by supervisors influence actual instructional practices at the traineeships of teachers in initial training? The descriptive and content analyzes supported the interpretation of the empirical data, collected through a questionnaire survey sent to 13 public polytechnic higher education institutions and semi-structured interviews to 6 trainees (future teachers). The results of the study reveal the different ways of conceiving the role of the supervisor and understand how the supervisory work was (or is not) mobilized as a device for building professional knowledge. We are, however, aware that in the human and social sciences, given the subjectivity of the phenomena under analysis, that the criteria of professional effectiveness as well as their factors are difficult to define and, above all, to measure.